ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC (Studi pada Bank Swasta yang Terdaftar di Bursa Efek Indonesia) - Edla Dianti; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Bank or banking is a pillar in building the Indonesian financial system and the economy because banks hanve a very important role as an intermediary institution is a financial institution that connects funds owned by units of the economic surplus economic units in need of funds. Bank performance that goes well will be able to support the growth of business for the bank’s role here is as a provider of investment funds and working capital for the business units in carrying out the production function. To the Bank Indonesian as regulator and supervisor directs the course of bank operations with the banking system development policy provisions in assessing the soundness of banks should be measured by the bank’s management in order to achieve stability in the financial system in order to boost national economic growth.This research is a quantitative descriptive study in order to determine and analyze the health of private banks in PT Bank Danamon Tbk, PT Bank CIMB Niaga Tbk and PT Bank Internasional Indonesia Tbk in 2010-2014 period by using RGEC method. The method of measuring the level of health by using ratios as indicators of NPL, LDR, NPM, ROA and CAR on the bank’s financial statements as the primary data.Results of research conducted average yield ratio and placement of components ratings show PT Bank Danamon Tbk of the 2010-2014 consecutive is categorized “HEALTHY” (PK-2), “HEALTHY” (PK-2), “HEALTHY” (PK-2), “HEALTHY” (PK-2), “HEALTHY” (PK-2). PT Bank CIMB Niaga Tbk of the 2010-2014 consecutive is categorized “HEALTHY” (PK-2), “HEALTHY” (PK-2), “VERY HEALTHY” (PK-1), “HEALTHY” (PK-2), “HEALTHY” (PK-2). PT Bank Internasional Indonesia Tbk of the 2010-2014 consecutive is categorized “HEALTHY” (PK-2), “HEALTHY ENOUGH” (PK-3), “HEALTHY” (PK-2), “HEALTHY” (PK-2), “HEALTHY ENOUGH” (PK-3).Keyword: The Health of Banks, Analytical Methods RGEC, Ratios NPL, LDR, NPM, ROA and CAR.